Performance evaluation of STATCOM placement in real-world power system through DOA-NVSP algorithm for congestion management and stability improvement - Tayo Uthman Badrudeen; Funso K. Ariyo; Nnamdi Nwulu (Scientific Reports)
Abstract The study presents an assessment of STATCOM placement in 28-bus, 330kV Nigerian power network (NPN) using a DOA-NVSP approach. The NVSP was employed to define the security status and predict the suitable placement of the STATCOM. Thereafter, the DOA was employed to optimally site and size the STATCOM. However, the search agents of the DOA algorithm were restricted to select the best suitable placement from the NVSP suggested locations. The DOA produces two best search agents based on their fitness factor- Alpha and Beta. The results from these two were further evaluated for performance improvement in terms of the stability and congestion management. The response plot graph on voltage profile was achieved by determining the degree of deviation of each search agent to reference or ideal bus voltage. Thereafter, the nonlinear least square (NLS) was employed to fit and compare the ideal operating voltage from Alpha and Beta STACOM sizing corresponding voltages. The Levenberg–Marquardt (LM) and trust-region (TR) algorithm were considered for the training of the NLS. The results from the NLS analysis show 0.0266, 0.3171 and 0.0340 for SSE, R-square and Rmse, respectively, for LM algorithm and 0.0220, 0.3890 and 0.0309 for SSE, R-square and Rmse, respectively, for TR algorithm. Similarly, the decongestion of the transmission line after STATCOM placement at bus 16 was 11.3% and 9.3% for active and reactive power, respectively. The study concluded that the proposed model was able to improve the stability and congestion management of the NPN.